Effect of application time of APF and NaF gels on microhardness and fluoride uptake of in vitro enamel caries - Delbem, Alberto Carlos Botazzo [UNESP]; Cury, Jaime A. (My University, 2002)
Purpose: To evaluate the effect of time of fluoride application gel, acidulated or neutral, on in vitro enamel resistance to demineralization and fluoride uptake. Materials and Methods: One hundred and ninety-two human enamel blocks were used in this study and 144 were treated with fluoride gel, acidulated or neutral, for 1 or 4 minutes. Ninety-six blocks treated with fluoride and 24 control blocks were submitted to a high cariogenic challenge. After the pH-cycling, enamel demineralization was assessed by surface and cross-sectional microhardness. Fluoride in the enamel blocks was also determined after removing an enamel layer by etching acid. Results: Acidulated fluoride gel formed more fluoride in enamel than neutral gel (P< 0.05), and it was also more efficient in reducing the demineralization of the enamel blocks submitted to a cariogenic challenge than the neutral one (P< 0.05). It was found that the time of application was significant in terms of fluoride uptake, but it did not render the enamel more resistant to demineralization.